The Proof is in the… Growing? A Peculiar Case of Kidney Stones. Issue 3 (July 2017) - Lombardi, Marco; Zoppi, Matteo; Bruschi, Piero; Selvi, Federico; Signorini, Maria Adele; Fanelli, Roberto; Michelassi, Stefano
A 45-year-old woman affected by MEN-1 syndrome with a history of bilateral nephrolithiasis due to parathyroid adenoma (primary hyperparathyroidism) and celiac disease presented to the nephrologist for recurrent episodes of renal colic and urinary passage of small stones with an unusual morphology despite previous surgical removal of the parathyroid adenoma. A complete diagnostic workup ought to be able to establish the type of stones, but contemporary medicine, with its reliance on protocols, procedures and scientific evidence, may have lost sight of the importance of good communication with the patient.